Protection masks - Zille, Andrea (2020)
In this video pill, Dr. Andrea Zille (researcher at 2C2T at the University of Minho and vice-president of Hipácia - Association of Italian Researchers in Portugal) talks about protection masks, answering questions such as: 2:32 How many types of masks exist? 6:11 How are masks made and what do they do? 7:56 How to put a mask on? 9:20 How to remove a face mask? For more information: https://www.who.int/ https://www.dgs.pt/ Hipácia - Association of Italian Researchers in Portugal Web https://www.hipacia.pt/ Facebook https://www.facebook.com/hipaciaporto... Twitter https://twitter.com/Hipacia1 YouTube https://www.youtube.com/channel/UCMWo... Instagram https://www.instagram.com/hipaciaport... Video Credits Produced by: Hipácia Presented by: Andrea Zille, PhD Edited by: Eleonora Zille Music: Lockdown_Song Music by: Stefan Kartenberg (c) Copyright 2020 Licensed under a Creative Commons Attribution Noncommercial (3.0) license. http://dig.ccmixter.org/files/JeffSpe... Ft: Javonelus